Novel biparametric MRI and targeted biopsy improves risk stratification in men with a clinical suspicion of prostate cancer (IMPROD Trial). Issue 4 (6th February 2017) - Jambor, Ivan; Boström, Peter J.; Taimen, Pekka; Syvänen, Kari; Kähkönen, Esa; Kallajoki, Markku; Perez, Ileana Montoya; Kauko, Tommi; Matomäki, Jaakko; Ettala, Otto; Merisaari, Harri; Kiviniemi, Aida; et al.
Abstract : Purpose: To evaluate the role of a 3T biparametric magnetic resonance imaging (bpMRI), T 2 ‐weighted imaging, and three separate diffusion‐weighted imaging acquisitions combined with targeted biopsy (TB) for improving risk stratification of men with elevated prostate‐specific antigen (PSA). Materials and Methods: Between March 2013 and February 2015, 175 men with a clinical suspicion of prostate cancer (PCa) were offered bpMRI (NCT01864135) based on a suspicion of PCa (two repeated PSA measurements in the range 2.5–20.0 ng/ml and/or abnormal digital rectal examination). Men with an equivocal to high suspicion of PCa had two TBs of the dominant lesion using cognitive ultrasound guidance, followed by systematic biopsy (SB). Men with a low to very low suspicion had only SB. In total, 161 (161/175, 92%) prospectively enrolled men completed the trial and were included in the final analyses. The primary endpoint of the trial was the cancer detection rate (CDR) of TB and SB. Clinically significant cancer (SPCa) was defined as Gleason score ≥3 + 4. Results: TB compared with SB had higher CDR for SPCa (45%, 72/161 vs. 39%, 63/161, respectively; P > 0.05) and a lower CDR for Gleason score 3 + 3 (8%, 15/161 vs. 16%, 30/161; P < 0.05). Restricting biopsy to men with equivocal to highly suspicious bpMRI findings would have resulted in a 24% (38/161) reduction in the number of men undergoing biopsy, while missing 4 (2%) with SPCa. All anonymized datasets, including bpMRI reports and follow up information, are freely available on the trial server. Conclusion: Prebiopsy bpMRI and TB in men with a clinical suspicion of PCa improved risk stratification. Level of Evidence: 1 Technical Efficacy: Stage 5 J. Magn. Reson. Imaging 2017;46:1089–1095.